Sistema web para auxílio no treinamento para maratonas de programação - Carneiro, Maurício Ferron (2012)
Programming contests, such as marathons and Olympics of programming, generally aim to test the ability of logical reasoning and speed of participants in solving computational problems. The training, based on problem solving, can help to improve the logical reasoning and speed of resolution. Thus, there was an opportunity to develop a system to provide web problems, support materials, solved problems, tips and guidelines. Lists of exercises can be composed from problems registered. The problems may be associated with troubleshooting tips. The system also allows the provision of functions implemented in code. The language used to implement the system is PHP with the implementation of Model-View-Controller. This pattern was chosen by the facilities provided, such as separation between interface, business logic and data access.